Kajian Komparatif Persepsi Guru terhadap Kompetensi Manajerial dan Supervisi Kepala Sekolah di Sekolah Negeri Dan Swasta Se-Kecamatan Cikarang Pusat - Saras Pangestu Sri Widowati; Sutirna; Undang Ruslan Wahyudin (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to comparatively analyze teachers’ perceptions of school principals’ managerial and supervisory competencies in public and private schools. Using a qualitative library research approach, the investigation was conducted from January to June 2024. Data were gathered through literature review of scholarly publications and school leadership policy documents, then subjected to descriptive-comparative analysis. Findings indicate that public school principals tend to employ structural-bureaucratic management with standardized supervision, whereas private school principals demonstrate greater flexibility and adaptive, clinical-collaborative supervision and planning. These differences are influenced by organizational culture, governance autonomy, and teachers’ professional experience. Private school teachers report higher satisfaction with supervision due to its responsiveness to their needs, while public school teachers value consistency and regulatory compliance. The study recommends developing a competency model for school principals that integrates flexibility and accountability, alongside strengthening continuous evaluation mechanisms to enhance leadership quality and learning outcomes.